Searching for Water: American Windmills in the Gardens of Fortaleza - Silva, Aline de Figueirôa (Anais do Museu Paulista: História e Cultura Material, 2017)
This article analyzes the relationship between environmental specificities and the cultivation of public gardens in the late nineteenth and early twentieth century in the city of Fortaleza, in the northeast region of Brazil. First, it examines the planted tree species and the creation of ponds in public gardens relative to hydric aspects and sun abundance in the city. Second, the essay describes the introduction of American windmills, known as cata-ventos in Brazil, by documenting their origin, their utility for pumping underground water stored in iron tanks, the use of this system for garden irrigation, as well as their disappearance. The paper uses iconographic and written documentary sources, such as newspapers, albums, magazines, photos, postcards, as well as chronicler’s reports and memoirs, and specialized literature on American windmills. Thus, it offers new references for garden historiography in Brazil concerning the existence of utilitarian artifacts for maintaining public gardens.